PERSEPSI PESERTA DIDIK TENTANG GURU MATA PELAJARAN DI SMP NEGERI 4 LUBUK ALUNG - Gunawan, Hendri - (Bimbingan dan Konseling, 2014)
The purpose of this study is to describe: (1) Perceptions of students about the mastery learning method by Indonesian teachers, (2) the perception of students on mastery learning media by Indonesian teachers, (3) perceptions of students on mastery learning materials by language teachers Indonesia. The shape of this research is descriptive quantitative research. The population in this study were all students at Junior High School 4 Lubuk Alung totaling 446 people and a sample of 82 people. This study used a stratified random sampling proportion that sampling of all members of the population at random and stratified proportionally. Means of collecting data of this study using a questionnaire. The data were processed using techniques percentage. The results of this study found that: (1). Perception of students about control methods by Indonesian teachers in Junior High School 4 Lubuk Alung included in either category, (2) perceptions of learners about the control of media by Indonesian teachers in Junior High School 4 Lubuk Alung included in either category, (3) perception of students on mastery of the material by the Indonesian teacher at Junior High School 4 Lubuk Alung included in either category